2021
DOI: 10.1002/stc.2810
|View full text |Cite
|
Sign up to set email alerts
|

A novel structural seismic protection system with negative stiffness and controllable damping

Abstract: In this paper, an innovative controllable negative stiffness system (CNSS) integrating adaptive negative stiffness and controllable damping characteristics is proposed to realise desirable vibration protection and improve adaptability, hence being effective to various earthquakes. The force-displacement relationship of the CNSS is derived as the forward model to describe its nonlinear properties. Three representative control algorithms, i.e., Linear Quadratic Regular (LQR) control, H∞ control and Sliding Mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Then a specific pseudo‐active actuator, the negative stiffness damper, is realized. Such a new concept of actuators with the combination of (variable) damping and (variable) negative stiffness was presented by Iemura and Pradono, 20,21 Weber and his associates, 22,23 Shi and Zhu, 24 and later Li's group 25,26 . All the theoretical results of their studies on the applications indicated that the new actuator could provide significant improvement on vibration attenuation, which is comparable to the system using an active actuator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then a specific pseudo‐active actuator, the negative stiffness damper, is realized. Such a new concept of actuators with the combination of (variable) damping and (variable) negative stiffness was presented by Iemura and Pradono, 20,21 Weber and his associates, 22,23 Shi and Zhu, 24 and later Li's group 25,26 . All the theoretical results of their studies on the applications indicated that the new actuator could provide significant improvement on vibration attenuation, which is comparable to the system using an active actuator.…”
Section: Introductionmentioning
confidence: 99%
“…A schematic of the force transition of a controllable damping actuator via a linear the combination of (variable) damping and (variable) negative stiffness was presented by Iemura and Pradono, 20,21 Weber and his associates, 22,23 Shi and Zhu, 24 and later Li's group. 25,26 All the theoretical results of their studies on the applications indicated that the new actuator could provide significant improvement on vibration attenuation, which is comparable to the system using an active actuator. Prototype realization of the new actuators with "controllable damping + negative stiffness" was only provided by Shi and Zhu 24 and Yang et al 27 A permanent magnet or an electromagnetic device was used for the negative stiffness capacity for such actuators.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been conducted on negativestifness damping devices and associated design theory. For instance, Li et al [49][50][51][52] analyzed the mechanism of negative stifness and proposed a novel controllable negative-stifness system using active control technology that can simultaneously achieve negative stifness and controllable damping properties. Using control algorithms (LQR control, H ∞ control, and sliding mode control), a controllable system based on full-state feedback was created, which improved vibration control performance on all evaluation criteria.…”
Section: Introductionmentioning
confidence: 99%
“…A small-scale coil spring unit and oil damper were designed and fabricated to build the Maxwell element. Because the negative stiffness devices that have been developed exhibit nonlinear behavior especially against large deformation, [44][45][46][47] we reduced the isolator stiffness instead.…”
Section: Introductionmentioning
confidence: 99%